DIGITAL MARKETING : STRATEGI YANG HARUS DILAKUKAN UMKM SAAT PANDEMI COVID-19 - Muchammad Saifuddin (Politeknik Ubaya, 2021)
Abstract This research is motivated by the existence of a pandemic covid 19 which is an obstacle for small and medium- sized enterprises (SMEs) in marketing. The purpose of this study was to provide an overview of the forms of digital marketing out by small-medium enterprises during the covid 19 pandemic that cannot be predicted for the end of the covid 19 pandemic. This research was descriptive qualitative one using a literature study with the focus to explain the results of research obtained by researchers. The results of this study was to provide an overview of digital marketing at the time of the covid-19 pandemic. Keywords: Digital Merketing, Marketing, covid-19, inbound marketing, outbond marketing